Influence of compliance of intramodular joints on the natural vibrations frequency of a modular building - V. S. Shirokov (Vestnik MGSU, 2023)
Introduction. The implementation of modular buildings leads to the necessity to develop methods of their calculation, including dynamic loads too. One of the main parameters in the calculation of loads from dynamic effects is the determination of natural frequencies of vibrations of the structure. The subject of research is the natural vibrational frequency of modular buildings. The aim of the research is to determine the effect of the compliance of intramodular joints on the vibrational frequencies of modular buildings.Materials and methods. The paper deals with the determination of the first natural frequency of vibration of a modular building with semi-rigid intramodular joints, and the influence of the compliance of the joints on the frequency. The author of the paper proposed and substantiated an analytical formula for determining the natural vibration frequencies, taking into account the stiffness parameters of modular buildings and the rigidity of intramodular joints. The proposed formula has sufficient accuracy for engineering calculations. At the same time, it allows to analyze the natural vibrational frequencies of modular buildings with different parameters without constructing calculation schemes in computer systems, which significantly speeds up the search for rational design solutions.Results. According to the obtained results, the discrepancy in the frequency values calculated by the finite element method and analytically for a one-story building with different ratios of the rotational stiffness of the joints does not exceed 1.5 %. For a multi-storey modular building, the difference in determining the natural vibration frequencies increases with the number of storeys, but does not exceed 10 % for three storeys.Conclusions. Based on the example of a modular building, it is shown that it is necessary to take into account the joint rigidity to determine the correct value of natural vibrational frequencies. Ignoring of the rotational stiffness of the joints can lead to an error in determining the dynamic effects.